Sources and distribution of yttrium and rare earth elements in surface sediments from Tagus estuary, Portugal - Brito, Pedro (2019)
The distribution and sources of yttrium and rare-earth elements (YREE) in surface sediments were studied on 78 samples collected in the Tagus estuary (SW Portugal, SW Europe). Yttrium and total REE contents ranged from 2.4 to 32mg·kg-1 and 18 to 210mg·kg-1, respectively, and exhibited significant correlations with sediment grain-size, Al, Fe, Mg and Mn, suggesting a preferential association to fine-grained material (e.g. aluminosilicates but also Al hydroxides and Fe oxyhydroxides). The PAAS (Post-Archean Australian Shale) normalized patterns display three distinct YREE fractionation pattern groups along the Tagus estuary: a first group, characterized by medium to coarse-grained material, a depleted and almost flat PAAS-normalized pattern, with a positive anomaly of Eu, representing one of the lithogenic components; a second group, characterized mainly by fine-grained sediment, with higher shale-normalized ratios and an enrichment of LREE relative to HREE, associated with waste water treatment plant (WWTP) outfalls, located in the northern margin; and, a third group, of fine-grained material, marked by a significant enrichment of Y, a depletion of Ce and an enrichment of HREE over LREE, located near an inactive chemical-industrial complex (e.g. pyrite roast plant, chemical and phosphorous fertilizer industries), in the southern margin. The data allow the quantification of the YREE contents and its spatial distribution in the surface sediments of the Tagus estuary, identifying the main potential sources and confirming the use of rare earth elements as tracers of anthropogenic activities in highly hydrodynamic estuaries.